Model of Health Care Support And Father Support for Mother on Children Under 2 Years Emotion in Blitar - Tri Riana Lestari; Tjipto Suwandi; Nursalam Nursalam; Moersintowarti B. Narendra (International Journal of Evaluation and Research in Education (IJERE), 2015)
Toddler stage is referred to as the golden era (golden age period), especially at the age of 0-2 years, the brain developmentreach 80%. This study examines the effects of healthcare support andf ather support for mother on the emotions of children aged under 2 years. This study was observational, with cross-sectional design.The sampling method in this research was multistage random sampling method in three sub districts and 20 villages. The total sample was 279 mothers and their children aged 3 months to 2 years in Blitar. Inferential data analysis using PLS (Partial Least Square) version 2.0.The result was that the children's emotions were formed by psychological factors of mother that affected by father factorsand health care support.